Longitudinal trajectories in renal function before and after heart failure hospitalization among patients with heart failure with preserved ejection fraction in the PARAGON‐HF trial. (15th August 2022) - Chatur, Safia; Vaduganathan, Muthiah; Peikert, Alexander; Claggett, Brian L.; McCausland, Finnian R.; Skali, Hicham; Pfeffer, Marc A.; Beldhuis, Iris E.; Kober, Lars; Seferovic, Petar; Lefkowitz, Martin; McMurray, John J.V.; et al.
Abstract : Aims: Worsening renal function may impact long‐term outcomes in heart failure (HF). However, little is known about the longitudinal trajectories in renal function in relation to HF hospitalization or how this high‐risk clinical event impacts renal outcomes. Methods and results: In PARAGON‐HF, we evaluated the association between recency of prior HF hospitalization (occurring pre‐randomization) and subsequent first renal composite outcome: (i) time to ≥50% decline in estimated glomerular filtration rate (eGFR); (ii) development of end‐stage renal disease; or (iii) death attributable to renal causes. A total of 2306 (48.1%) patients had a history of prior HF hospitalization. Incident rates of the renal outcome were highest in those most recently hospitalized and decreased with longer time from last hospitalization. Treatment effect on the renal outcome of sacubitril/valsartan versus valsartan was similar between patients with (hazard ratio [HR] 0.43; 95% confidence interval [CI] 0.24–0.76) and without (HR 0.63; 95% CI: 0.33–1.18; p interaction  = 0.39) a prior history of HF hospitalization and appeared consistent regardless of timing of prior hospitalization for HF ( p interaction  = 0.39). Serial eGFR measurements leading up to and after a HF hospitalization (occurring during the study period) and estimated eGFR trajectories using repeated measures regression models with restricted cubic splines were also examined. Patients experiencing a post‐randomization HF hospitalization had a significant decline in eGFR prior to hospitalization while patients without HF hospitalization experienced a relatively stable eGFR trajectory ( p  < 0.001). A change in the rate of decline of eGFR trajectory was observed 12 months preceding a HF hospitalization, and continued in the post‐discharge window to 12 months following hospitalization. Conclusions: Heart failure hospitalization denotes increased risk for kidney disease progression which continues following recovery from HF decompensation in patients with HF with preserved ejection fraction. Clinical Trial Registration: PARAGON‐HF (Prospective Comparison of ARNI with ARB Global Outcomes in HF with Preserved Ejection Fraction), ClinicalTrials.gov NCT01920711. Abstract : Longitudinal trajectories in renal function before and after heart failure hospitalization (HFH) in Patients with heart failure with preserved ejection fraction (HFpEF). eGFR, estimated glomerular filtration rate; HF, heart failure.